Effect of organic mineral fertilizers and growth regulator on winter durum wheat crops under irrigation conditions in the Terek-Sulak subprovince of the republic of Dagestan - N. R. Magomedov; A. A. Abdullaev; Zh. N. Abdullaev; T. T. Babaev (Зерновое хозяйство России)
The current study has been carried out to determine the effect of mineral and organic mineral fertilizers, as well as a growth regulator on the productivity of promising winter durum wheat varieties, under irrigation conditions of meadow-chestnut heavy loamy soil in the Terek-Sulak subprovince of the Republic of Dagestan. In 2019–2021 there were laid on two trials on the experimental plot. In the first case, there were studied four variants of the effect of fertilizers on the productivity of promising varieties ‘Krupinka’ (control), ‘Krucha’, ‘Odari’ under irrigation conditions. There was used ammophos (background), 65 kg/ha a.i. under plowing; ammophos (background), 65 kg/ha a.i. for plowing + Polydon bio universal, 0.5 l/ha in the tillering phase + Polydon bio universal, 0.5 l/ha in the earing phase; ammophos (background), 65 kg/ha a.i. under arable land + ammonium nitrate 150 kg/ha in spring tillering + Polydon bio universal 0.5 l/ha in the tillering phase + Polydon bio universal 0.5 l/ha in the earing phase; ammophos (background), 65kg/ha a.i. for plowing + ammonium nitrate 150 kg/ha in spring tillering. In the second, three winter durum wheat varieties were treated before sowing with 0.5 l/t of Sprintalga and foliar top dressing was carried out in the spring tillering phase, in comparison with the control when seeds were treated with 10 l/t of the working liquid disinfectant Maxim KS. The conducted study has shown that the largest productivity of the studied winter durum wheat varieties was achieved in the third variant of the trial, where grain productivity of 8.36 t/ha was achieved for the variety ‘Odari’, the variety ‘Krucha’ was in second place with 7.91 t/ha of productivity, which was on 0.27 t/ha more than for the control variety ‘Krupinka’ and on 0.45 t/ha less than in the variety ‘Odari’. The use of a growth regulator has shown its significant effect on the grain productivity improvement. Seed treatment of winter durum wheat varieties and crops in the tillering phase with Sprintalgi had a positive effect on the growth, development, and improvement of grain yield. On average, over the years of research, the largest grain yield of 7.88 t / ha was obtained for the variety ‘Odari’, in the variant of seed and crop treatment with a growth regulator Sprintalgi. The productivity difference in the variant with seed treatment with Sprintalgi and with the working liquid treater Maxim KS was 0.67 t/ha for the variety ‘Odari’, 0.71 t/ha for ‘Krucha’ and 0.79 t/ha for ‘Krupinka’.